Heritability, genetic correlation and linkage to the 9p21.3 region of mixed platelet–leukocyte conjugates in families with and without early myocardial infarction - Gianfagna, F.; Tamburrelli, C.; Vohnout, B.; Crescente, M.; Izzi, B.; Pampuch, A.; De Curtis, A.; Di Castelnuovo, A.; Cutrone, A.; Napoleone, E.; Tayo, B.; Lorenzet, R.; et al. (Nutrition, metabolism, and cardiovascular diseases, 2013)
Variations in mixed platelet–leukocyte conjugate formation in human whole blood could be genetically determined. We quantified platelet and leukocyte activation and interaction in families with or without early myocardial infarction and evaluated their heritability, genetic correlation and linkage to the 9p21.3 region. The study population included 739 subjects (≥15 years old) from 54 large pedigrees, 23 with and 31 without familial myocardial infarction. Mixed platelet–leukocyte conjugates and markers of platelet or leukocyte activation (P-selectin, CD11b and L-selectin surface expression) were measured both before and after in vitro blood stimulation with collagen-ADP. All traits had significant genetic components (17.5–65.3% of the phenotypic variability), while shared household effects (0–39.6%) and environmental covariates (0–10.2%) tended to be smaller. Stimulated platelet-polymorphonuclear leukocyte (PMN) and platelet–monocyte conjugates showed the highest linkage to the 9p21.3 region (LOD = 0.94 and 1.33, respectively; empirical p value = 0.017 and 0.009). PMN markers resulted strongly genetically correlated between them in bivariate analysis among pairs of quantitative traits. This study supports a genetic regulation of human mixed platelet–leukocyte conjugates.